Drivers of Viral Prevalence in Landscape‐Scale Pollinator Networks Across Europe: Honey Bee Viral Density, Niche Overlap With This Reservoir Host and Network Architecture - Willem Proesmans; Cedric Alaux; Matthias Albrecht; Karima Bassit; Nathan Cyrille; Anne Dalmon; Virginie Diévart; Christophe Dominik; Emeline Felten; Anna Gajda; Jonna M. Heuschele; Emilien Laurent; et al. (Ecology Letters, 2026)
Viral transfer from managed pollinators potentially threatens wild pollinators and may be exacerbated by land‐use changes. Our causal models and plant‐pollinator network data from 48 European urban and agricultural landscapes revealed the ecological mechanisms underpinning viral transmission. Host identity, network architecture and land‐use modulated viral dynamics (black queen cell virus, BQCV; deformed wing virus, DWV‐A and DWV‐B). Viral prevalence in wild pollinators was driven by viral density in the reservoir host: honey bees, and secondarily by trophic niche overlap with these managed pollinators. Modular networks limited BQCV prevalence, which was driven by reduced honey bee niche overlap, suggesting minimal onward transmission among wild pollinators. Landscapes supporting greater wild pollinator abundance diluted DWV‐B transmission; in urban landscapes managed honey bees and wild pollinators experienced higher and lower BQCV prevalence, respectively. Disease in managed bee colonies and land‐use changes that concentrate pollinator foraging interactions present potential viral risks to wild pollinator health.